Externalizing and internalizing symptoms in childhood and adolescence and the risk of alcohol use disorders in young adulthood: A meta-analysis of longitudinal studies. (October 2019) - Meque, Ivete; Dachew, Berihun Assefa; Maravilla, Joemer C; Salom, Caroline; Alati, Rosa
Background: Evidence suggests that externalizing and internalizing symptoms are expressed early in life and are associated with problematic drinking in young adulthood. However, few studies have examined their role during childhood and adolescence in predicting alcohol problems later in life. Objectives: To examine the role of childhood and adolescent externalizing and internalizing symptoms in predicting alcohol use disorders in young adulthood. Methods: We searched five electronic databases (PubMed, Scopus, PsycINFO, Web of Sciences and Embase) for studies which diagnosed alcohol use disorders through either the International Classification of Diseases or American Psychiatric Association – Diagnostic and Statistical Manual of Mental Disorders criteria and followed up children or adolescents into the transition to young adulthood. We performed a meta-analysis and obtained pooled odds ratio estimates with 95% confidence intervals using random-effects models. Results: A total of 12 longitudinal studies met eligibility criteria and were included in the meta-analysis. All measured the outcome using Diagnostic and Statistical Manual of Mental Disorders criteria. The majority were of good quality and were conducted in the United States. A total of 19, 407 participants (50% female) were included in this meta-analysis. Of these, n = 2337 (12%) had diagnoses of alcohol use disorders/alcohol dependence. Participant ages ranged from birth to 36 years. Internalizing symptoms increased the risk of young adult alcohol use disorders by 21% (odds ratio = 1.21; 95% confidence interval = [1.05, 1.39]), with no strong evidence of publication bias. Subgroup analysis suggested significantly lower heterogeneity than for externalizing studies. Externalizing symptoms increased the risk of alcohol use disorders by 62% (odds ratio = 1.62, 95% confidence interval = [1.39, 1.90]). We found some evidence of publication bias and significant heterogeneity in the studies. Conclusion: Our findings highlight the contribution of early behavioural problems to the development of alcohol use disorders in young adulthood and the need for timely scrutiny of and intervention on early behavioural problems.